Aripiprazole differentially regulates the expression of Gad67 and γ-aminobutyric acid transporters in rat brain - Peselmann, Nina; Gebicke-Härter, Peter J.; Zink, Mathias (European archives of psychiatry and clinical neuroscience, 2013)
The molecular etiology of schizophrenia comprises abnormal neurotransmission of the amino acid GABA (γ-aminobutyric acid). Neuropathological studies convincingly revealed reduced expression of glutamic acid decarboxylase (Gad67) in GABAergic interneurons. Several antipsychotics influence the expression of GABAergic genes, but aripiprazole (APZ), a partial dopaminergic and serotonergic receptor agonist, has not been involved into these studies so far. We treated Sprague-Dawley rats for 4 weeks or 4 months with APZ suspended in drinking water and doses of 10 and 40 mg per kg body weight. Gene expression of Gad67, the vesicular GABA transporter Slc32a1 (solute carrier family, Vgat), the transmembrane transporters Slc6a1 (Gat1) and Slc6a11 (Gat3) was assessed by semiquantitative radioactive in situ hybridization. APZ treatment resulted in time- and dose-dependent effects with qualitative differences between brain regions. In the 10-mg group, Slc6a1 was strongly induced after 4 weeks in the hippocampus, amygdala, and cerebral cortex, followed by an induction of Gad67 in the same regions after 4 months, while frontocortical regions as well as basal ganglia showed dose-dependent reductions of Gad67 expression after 4 months. In several frontocortical and subcortical regions, we observed a decrease of Slc32a1 and an increase of Slc6a11 expression. In conclusion, APZ modulates gene expression of GABAergic marker genes involved into pathogenetic theories of schizophrenia. APZ only partially mirrors the effects of other antipsychotics with some important differences regarding brain regions. The findings might be explained by regulatory connections between serotonergic, GABAergic, and dopaminergic neurotransmission and should be validated in behavioral animal models of psychotic disorders.